A Systematic Review of the Provision of Sexuality Education to Student Teachers in Initial Teacher Education - Costello, Aisling; Maunsell, Catherine; Cullen, Claire; Bourke, Ashling (Frontiers in Education, 2022)
Understanding sexuality education during initial teacher education is crucial to the delivery of successful sexuality education provision in schools. This systematic review reports on empirical studies published in English from 1990 to 2019. In accordance with the PRISMA guidelines, five databases were searched: ERIC, Education Research Complete, PsycINFO, Web of Science and MEDLINE. From a possible 1153 titles and abstracts identified, 15 papers were selected for review. Findings are reported in relation to the WHO-BZgA (2017) Training Matters: Framework of core competencies for sexuality educators. Results revealed that research on sexuality education during initial teacher education is limited and minimal research has investigated students teachers' attitudes on sexuality education. Findings indicate that the sexuality education provision received is varied and not reflective of comprehensive sexuality education. Recommendations highlight the need for robust research to inform quality teacher professional development practices to support teachers to develop the knowledge, attitudes and skills necessary to teach comprehensive sexuality education.